Interferência e estudos fitossociológicos da comunidade infestante na cultura do sorgo sacarino - Giancotti, P. R.F. [UNESP]; Moro, M. S. [UNESP]; Nepomuceno, M. P. [UNESP]; Barroso, A. A.M. [UNESP]; Martins, P. F.R.B. [UNESP]; Alves, P. L.C.A. [UNESP] (FapUNIFESP (SciELO), 2017)
This research was carried out to evaluate the interference periods and phytosociological indexes of the weed community on sweet sorghum, hybrid CVSW 80007, cultivated for two seasons in a year. The treatments were based on an increased duration of weed presence and weed absence after sowing (0, 4, 7, 14, 21, 28, 35, 42, 56 and 68 days after crop emergence for the summer season and 0, 4, 7, 14, 21, 28, 35, 42, 49, 56, 63 and 100 days for the fall season). The weed community was evaluated based on the number of weeds and the dry mass of each weed population in each period of weed control in the summer season and each period of no weed control and weed control in the autumn season. These data were used to determine the relative indexes of density, dominance and importance, and the weed community indexes of diversity and equitability. The main weeds comprising the community were Cyperus rotundus, Alternanthera tenella, Indigofera hirsuta, Amaranthus sp., Digitaria nuda, and Portulaca oleracea. The weed density was found to be the primary factor for the importance of weeds in the community, once their development and biomass accumulation were suppressed by the sweet sorghum competition. The sweet sorghum hybrid proved highly competitive and, in the agro-ecological conditions of the trials, weed interference did not reduce crop yield.
Weed community interference and phytosociological studies in a sweet sorghum crop
Keywords: Sorghum bicolor; Weed competition; Weeds